PENGARUH PERILAKU KEPEMIMPINAN, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN PEGAWAI PADA KANTOR IMIGRASI KELAS I TPI KENDARI - Norna Ulfah Sayuti; Ibnu Hajar; Ummy Kalsum (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine: (1) The influence of leadership behavior, work environment, and job satisfaction simultaneously affect employee commitment at the Immigration Office Class I TPI Kendari. (2) The influence of leadership behavior on employee commitment at the Immigration Office Class I TPI Kendari. (3) The influence of the work environment on employee commitment at the Immigration Office Class I TPI Kendari. (4) The effect of job satisfaction on employee commitment to Class I Immigration Office TPI Kendari. The study population was all employees of the TPI Kendari Class I Immigration Office, namely as many as 76 excluding the leadership, the research data was collected using a questionnaire and processed using the SPSS statistical application. The results of this study indicate that: (1) leadership behavior, work environment, and job satisfaction simultaneously have a positive and significant effect on employee commitment at the Immigration Office Class I TPI Kendari. (2) leadership behavior has a positive and significant effect on employee commitment at the Immigration Office Class I TPI Kendari. (3) work environment has a positive and significant effect on employee commitment at the Immigration Office Class I TPI Kendari (4) job satisfaction has a positive and significant effect on employee commitment at the Immigration Office Class I TPI Kendari